OXIDATION OF ORGANIC SUBSTRATES OF DIFFERENT NATURES IN THE PRESENCE OF HUMIC AND HEMATOMELANIC ACIDS - ЄФІМОВА, І. В.; СМИРНОВА, О. В.; БЕССАРАБОВ, В. І. (Technologies and Engineering, 2023)
Purpose. Establishment of the physicochemical regularities of the oxidation of various organic substrates in the presence of humic and hematomelanic acids from brown coal, as well as the identification of the possibility of regulating the antioxidant and prooxidant properties of these supramolecular inhibitory systems in the processes of radical chain oxidation. Methodology. The oxidation of cumene, ethylbenzene and ascorbic acid initiated by azodiisobutyronitrile in the presence of humic and hematomelanoic acids in an aprotic medium was investigated by gas volumetric method. Results. The initiated liquid-phase oxidation of cumene and ethylbenzene by oxygen in the presence of humic and hematomelanic acids from brown coal has been studied. It is shown that the addition of humic substances to the studied system causes inhibition of the oxidation process of these model substrates, and the observed effect increases with increasing concentration of humic substances. The initiated liquid-phase oxidation of ascorbic acid by oxygen in the presence of humic and hematomelanic acids from brown coal is studied. It is shown that the addition of humic substances to the studied system causes acceleration of the oxidation process of this model substrate, and the observed effect increases with increasing concentration of humic substances. Scientific novelty. For the first time, the selective antioxidant or prooxidant activity of humic and hematomelanic acids in the processes of radical-chain oxidation, depending on the nature of the oxidizing substrate, was proven. Practical significance. Studies show that humic substances exhibit selective properties that slow down or accelerate the processes of radical-chain oxidation depending on the nature of the oxidized substrate. The ability of humic and hymatomelanoic acids to antioxidant and prooxidant activity can be promising for the creation of complex drugs with targeted action with regulated redox properties. Since macromolecules of humic and hymatomelanic acids are nanosized natural formations, the development of antioxidants and prooxidants based on them is promising from the point of view of nanomedicine.